The Relationship between Age, Working Period, and Duration of Work with Work Fatigue in Online Taxi Drivers in Yogyakarta City - Qulubil Malaikie, Roudhotan; Dwi Saptadi, Julian (Universitas Ahmad Dahlan, 2025)
Background: Fatigue is a physical and mental condition that can reduce the ability to work and weaken the body's resistance during activities. The job as a driver demands high concentration because it requires quick and precise coordination between the brain, hands, feet, and eyes, making it susceptible to fatigue. Continuous fatigue not only has an impact on decreased performance, but also increases the risk of work accidents and endangers the safety of passengers and drivers themselves. Based on this, this study aims to determine the relationship between age, working period, and duration of work and work fatigue in online taxi drivers in Yogyakarta City, so that the results are expected to be considered in efforts to prevent and manage the risk of work fatigue in the online transportation sector. Methods: This study used a quantitative approach with a cross-sectional design. The sample studied consisted of 54 online taxi drivers taken from three online taxi driver associations. The sampling technique used is stratified random sampling. A tool for collecting data is in the form of IFRC questionnaires. Data analysis was carried out using the Pearson correlation test. This requires that the data meet the normal distribution assumptions. If this assumption is not met, an alternative Spearman Rank test is used. Results: Age was not significantly related to the fatigue of online taxi drivers in Yogyakarta (p=0.881>0.05). In contrast, working time (p=0.002<0.05) and duration of work (p<0.001<0.05) showed a significant relationship with work fatigue. Conclusion: There is a significant association between working time and duration of work with fatigue levels, however, no significant association was found between age and work fatigue in online taxi drivers in the city of Yogyakarta.